Performance Status in Elderly Cancer Patients Attending at Tertiary Cancer Center, Nepal - Pokhrel, Sunita; Neupane, Laxmi; Sharma, Sarojini; Koirala, Sushila (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Globally, the elderly population is increasing rapidly. Along with age, cancer and other co-existing medical conditions affect the performance status of the elderly. It plays a key role in treatment decisions and is an independent prognostic indicator. The objective of the study was to assess the performance status of elderly cancer patients attending the Tertiary Cancer Centre in Nepal.Method: A descriptive cross-sectional study was conducted among 100 elderly cancer patients admitted for treatment. Purposive sampling was used, and data were collected via face-to-face interviews. Data were entered and analysed by using SPSS version 20. Descriptive and inferential statistics were calculated.Result: The respondents’ ages ranged from 60 to 82 years, with a mean and standard deviation of 66±5.32. The majority of respondents were in the 60-69 age group. Twenty-five respondents were in stage IV. The majority of respondents have surgery for treatment (71.0%). Pain was the most common (57.0%) side effect experienced by respondents, and performance status was affected by side effects among 66.0%. Co-morbidities were present among 64.0% and among them, 71.0% had hypertension. More than half of the respondents had a good ECOG performance status (51.0%) and were independent in functional status (55.0%). There is a significant association between level of ECOG performance status with age (p-value =0.011), staging (p-value=0.029), and co morbidities (p-value=0.042).Conclusion: The study showed that over half of the respondents had good ECOG scores and were functionally independent, highlighting the need for stronger primary and secondary prevention efforts to support early diagnosis and better performance status.